Tinjauan Prosedur Isian Informed Consent Pada Operasi Katarak di Rumah Sakit Umum X Kediri - Indah Susilowati; Weni Rosita (Yayasan Literasi Sains Indonesia, 2022)
The statement form containing the consent of the patient or his family after receiving a complete explanation regarding the medical action taken is called Informed Consent. The form must be filled out completely, clearly, and according to the established procedure. The purpose of the study was to determine the suitability of the procedure in filling out informed consent for cataract surgery at RSU X Kediri. The type of research is case study, a retrospective approach. The population of medical record documents at RSU X Kediri are 605 cataract surgery patients in 2020, and the sample is 86 cataract surgery informed consent forms. The results of the study, there are policies and standard procedures regarding how to fill out Informed Consent data, In the completeness of the Informed Consent form for cataract surgery 34 (40%) are completely filled, while 52 (60%), are not completely filled out in some items from Patient Identification, Report Important, Authentication. In conclusion, there are policies and standard procedures at RSU X Kediri that have not been implemented according to the rules, because there are still incomplete data findings filled in in the informed consent. The advice is to disseminate the importance of consistency in filling out Informed Consent and evaluate of compliance with procedures to protect health workers from lawsuits in the future